2018
DOI: 10.1242/jeb.190587
|View full text |Cite
|
Sign up to set email alerts
|

Lateral line sensitivity in free swimming toadfish,Opsanus tau

Abstract: A longstanding question in aquatic animal sensory physiology is the impact of self-generated movement on lateral line sensitivity. One hypothesis is that efferent modulation of the sensory hair cells cancels self-generated noise and allows fish to sample their surroundings while swimming. In this study, microwire electrodes were chronically implanted into the anterior lateral line nerve of oyster toadfish and neural activity was monitored during forward movement. Fish were allowed to freely swim or were moved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…We still know relatively little about efferent modulation in freely-swimming fishes, where hydrodynamic stimuli from swimming can further impact afferent activity, but we now have a greater appreciation for the complex relationship between sensory and motor systems. In freely moving fish, afferent spike frequencies increase both during swimming and during feeding strikes (Palmer et al 2005; Palmer et al 2003; Ayali et al 2009; Mensinger et al 2019). This is consistent with our observation that efferent activity only partially suppresses spontaneous spike rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We still know relatively little about efferent modulation in freely-swimming fishes, where hydrodynamic stimuli from swimming can further impact afferent activity, but we now have a greater appreciation for the complex relationship between sensory and motor systems. In freely moving fish, afferent spike frequencies increase both during swimming and during feeding strikes (Palmer et al 2005; Palmer et al 2003; Ayali et al 2009; Mensinger et al 2019). This is consistent with our observation that efferent activity only partially suppresses spontaneous spike rates.…”
Section: Discussionmentioning
confidence: 99%
“…Fishes sense perturbations in the fluid environment through the lateral line, a sensory organ on the body surface that translates fluid motion relative to the body into neural signals essential for navigation (Olszewski, et al 2012, Suli et al 2012, Oteiza et al 2017), predator avoidance, prey capture (McHenry et al 2009; Stewart et al 2013), and schooling (Mekdara et al 2018). However, since water motions are also self-generated by behaviors such as swimming (Palmer et al 2003; Ayali et al 2009; Mensinger et al 2019), respiration (Montgomery et al 1996; Montgomery and Bodznick 1994; Palmer et al 2003), and feeding (Palmer et al 2005), fishes should possess a mechanism to discriminate such self-generated signals from environmental signals.…”
Section: Introductionmentioning
confidence: 99%
“…Fishes sense perturbations in the fluid environment through the lateral line, a sensory organ on the body surface that translates fluid motion relative to the body into neural signals essential for navigation (Olszewski, et al 2012;Oteiza et al 2017;Suli et al 2012), predator avoidance, prey capture (McHenry et al 2009;Stewart et al 2013), and schooling (Mekdara et al 2018). However, since water motions are also self-generated by behaviors such as swimming (Ayali et al 2009;Mensinger et al 2019;Palmer et al 2003), respiration (Montgomery et al 1996;Montgomery and Bodznick 1994;Palmer et al 2003), and feeding (Palmer et al 2005), fishes should possess a mechanism to discriminate such self-generated signals from environmental signals.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged inhibition during these ongoing behaviors seems unlikely as responses to important external stimuli would be inhibited as well. A recent study in toadfish indeed found that the lateral line system remains sensitive to external stimuli in spite of selfstimulation generated by swimming (Mensinger et al, 2018). It appears that a more dynamic filter would be useful under most circumstances and evidence for predictive cancellation of reafference was briefly reported in the MON of the teleost scorpion fish, but this has not been further studied (Montgomery and Bodznick, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This could reduce reafference by turning off the receptors during behavior, but the efferents appear only to be activated during very vigorous behaviors that threaten to overdrive receptors (Bodznick, 1989;Roberts and Russell, 1972). The requisite movements of behaviors such as ventilation and swimming cause self-stimulation that drives lateral line primary afferent responses (Montgomery et al, 1996;Russell and Roberts, 1974;Palmer et al, 2005;Ayali et al, 2009;Mensinger et al, 2018). However, second-order cells are not driven by the same self-stimulation, at least in the case of ventilation (Montgomery et al, 1996).…”
Section: Introductionmentioning
confidence: 99%